2022
DOI: 10.3389/fpsyg.2022.941404
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between emotion regulation strategies and total conviction in promoting behavior change

Abstract: Research conducted in the recent past have proposed total conviction as a factor associated with cognitive reappraisal that may produce changes in emotion and behavior. However, the factors that influence total conviction are not yet clearly identified. In this study, we focused on daily emotion regulation strategies and examined the relationship between emotion regulation strategies and total conviction. A total of 42 undergraduate and graduate students participated in this study. They measured their tendency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Instead, suppression tendency was shown to regulate the association between total conviction and behavior change. 37…”
Section: Discussionmentioning
confidence: 99%
“…Instead, suppression tendency was shown to regulate the association between total conviction and behavior change. 37…”
Section: Discussionmentioning
confidence: 99%
“…While maintaining a strong belief in the chosen strategy, leaders must be adaptable and open to adjusting their approach based on ongoing feedback and changing circumstances. This adaptability isn't a sign of wavering conviction but a demonstration of the strategic agility necessary to navigate dynamic environments successfully (Shigematsu & Kobayashi, 2022).…”
Section: Strategic Convictionmentioning
confidence: 99%
“…Neurologists have further corroborated the mode of action of different emotion regulation strategies through functional MRI, potential recognition, and more ( 27 , 28 ). Emotion regulation strategies have been applied in neurological disorders treatment, time perception, and psychological support and interventions ( 29 31 ). Studies have shown that cognitive reappraisal is beneficial in relieving emotions such as anxiety and depression, while expression suppression has the opposite effect ( 32 34 ).…”
Section: Introductionmentioning
confidence: 99%